(untitled) - Bash, Lee (Bolton, MA, 2003)
The book begins with an overview of adult-learning programs, followed by an examination of significant differences between adult students and their younger classmates. Mr. Bash looks at why adults are choosing to continue their education, and he discusses the particular challenges that they have to contend with, not the least of which are "pursuing studies when their responsibilities are already likely to be overextended, and placing themselves into an environment they often perceive as hostile and frightening."
Keywords: Adult learning,Adult education; Người lớn học tập,Giáo dục người lớn